Penyuluhan Pengetahuan Tentang Menstruasi dengan Perilaku Personal Hygiene Saat Menstruasi pada Remaja Putri di Desa Sutawinangun Kecamatan Kedawung Kabupaten Cirebon - Sofiyati Sofiyati (Jurnal Nusantara Berbakti, 2023)
Menstruation or menstruation is the discharge of blood from the uterus through the vagina which occurs once a month and starts at the age of 12 to 15 years. Usually the menstrual period is between 3 and 7 days. The arrival of the first menstruation is not the same for every teenager. Lack of knowledge about menstruation and dealing with pain during menstruation by young women will have a negative impact on life. Poor menstrual personal hygiene has a major effect on morbidity and complications. Therefore, adolescents must be prepared in terms of knowledge, attitudes and actions towards achieving healthy reproduction. Menstrual hygiene is most likely influenced by the level of knowledge about reproductive health. Stakeholders should further increase public understanding, especially young women, about menstruation by providing education in the form of counseling or other information media so that this information can be reached and accepted by the community, especially young women.